STRUCTURE MODELLING OF SUBSURFACE BY USING KIRCHHOFF MIGRATION METHOD AND FINITE DIFFERENCE ANISOTROPY METHOD - Husni Cahyadi Kurniawan; Adi Susilo; Teguh Suroso (Department of Physics, Sebelas Maret University, 2017)
The image of subsurface with a migration method keeps on developing to get an image result which the closest in real condition. The conditions in subsurface are very complex and variables it couses the process of wave propagation which can not be judged as the same in every layers. so it is needed an anisotropy pharameter analysiz (η) in seismic data migration process. The research will compare two kinds of migrations those are Kirchhoff migration and finite difference anisotropy. It is done because not all datas are processed by anisotropy, even with isotropi it will get good result. The result of kirchoff migration has not so good quality (low resolution) on the first layer reflector.but on the second and third layer reflector have good result (high resolution). I estimate that in the first layer reflector there is anistropi influence, because the ratio effect between far offset and the depth is hight. The analysis result get η ansotropi pharameter result as 0,25 and put into migration process. On the second migration process is finite difference anisotropy appears on the first layer reflector and shows high resolution and suitable with the real layer model.